Fixed Drug Eruption Caused by Etoricoxib - Catherine, Niya (Indian Journal of Pharmacy Practice)
Etoricoxib is a COX 2 selective inhibitor it has one of the highest cox 2 selectivity and is one of the newer coxib class drug. Etoricoxib is an orally active cox 2 selective inhibitor that acts by blocking the cox 2 enzyme thereby reducing the formation of pro inflammatory prostaglandins without significantly affecting cox 1, which helps maintain GI protection and platelet function. Etoricoxib belongs to the NSAIDS class and exhibits anti-inflammatory, analgesic and antipyretic properties. A 56-year-old female patient was admitted for the management of hypertension. During her history taking she reported a highly pigmented deep bruise in her right thigh. She was diagnosed with osteoarthritis 2 years back and had been taking oral Etoricoxib 90 mg for pain management for the past 1 year. Overtime she noticed that a black discoloured bruise started appearing on her upper thigh. On examination it was confirmed that a fixed drug eruption was likely caused by prolonged Etoricoxib use. The medication was discontinued and tramadol 40 mg was prescribed for pain relief. Fusidic acid cream was applied locally to aid skin recovery. This case highlights the importance of use of NSAIDS like Etoricoxib particularly in long term therapy. Prolonged use can lead to adverse effects such as fixed drug eruptions and unexplained bruising. Regular monitoring, early identification of side effects and timely withdrawal of the offending drug are essential to prevent complications and ensure patients.
Keywords: ADRs; Etoricoxib; NSAIDS; Fixed Drug Eruptions